2019
DOI: 10.3390/cancers11020249
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Analysis in Tumor-Draining Pulmonary Vein Identifies NSCLC Patients with Higher Risk of Relapse after Curative Surgery

Abstract: Since tumor-draining pulmonary vein blood (PV) is enriched in tumor-secreted products, we hypothesized that it would also be enriched in tumor-derived exosomes, which would be important in the metastasis process. We characterized exosomes from PV of 61 resected non-small cell lung cancer (NSCLC) patients to evaluate its potential as relapse biomarkers. Exosomes were characterized using transmission electron microscopy, western blot and nanoparticle tracking analysis and we examined time to relapse (TTR) and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…In a recent study, by screening the pulmonary vein-derived exosomes in a cohort of 72 resected NSCLC patients, Navarro and colleagues showed that exosome size (cut-off: 112 nm) was able to discriminate relapsed patients with a higher accuracy than clinical data (stage and lymph node involvement). In the multivariate analysis, exosome size resulted an independent risk factor for both time to relapse (HR: 6.66; 95% CI, 2.06-21.51; p = 0.001) and OS (HR: 4.55; 95% CI, 1.43-14.49; p = 0.010) [78]. Whatever their dimension, exosomes have an active role in the process of carcinogenesis, progression, and metastasis of several tumors, including NSCLC, which is exerted by transferring their cargo.…”
Section: Exosomesmentioning
confidence: 97%
“…In a recent study, by screening the pulmonary vein-derived exosomes in a cohort of 72 resected NSCLC patients, Navarro and colleagues showed that exosome size (cut-off: 112 nm) was able to discriminate relapsed patients with a higher accuracy than clinical data (stage and lymph node involvement). In the multivariate analysis, exosome size resulted an independent risk factor for both time to relapse (HR: 6.66; 95% CI, 2.06-21.51; p = 0.001) and OS (HR: 4.55; 95% CI, 1.43-14.49; p = 0.010) [78]. Whatever their dimension, exosomes have an active role in the process of carcinogenesis, progression, and metastasis of several tumors, including NSCLC, which is exerted by transferring their cargo.…”
Section: Exosomesmentioning
confidence: 97%
“…For example, in melanoma patients, lymphatic exudate contains more cancer-derived EVs than plasma, and lymph vessels were shown to be the major route of EV transport from tumors into the circulation [ 192 , 193 ]. In lung cancer, tumor-draining pulmonary venous blood contains more cancer-derived EVs than peripheral blood [ 194 ]. Further studies are needed to develop standard protocols for sampling different biofluids and isolating EVs from them, as well as for establishing the diagnostic accuracy of those EVs.…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…Thus, the balance between pro-coagulant and anti-coagulant properties of the platelet-derived vesicles plays an important role in supporting of hemostasis [24,25] . Intriguingly, there is evidence that the platelet-derived vesicles are cargo for several molecules, including chromatin, hormones, proteins, which mediate cell-to-cell cooperation, immune reaction, inflammatory response, and reparation [18][19][20][21][22] . It has been found that the main fraction of miRNA is localized in the platelet-derived vesicles, which protect miRNA from degradation in the circulation.…”
Section: Platelet-derived Vesiclesmentioning
confidence: 99%
“…The populations of the Figure 1. The proportions and functions of several types of extracellular vesicles in circulation [20][21][22][23] . APC: antigen presenting cells platelet-derived EVs may distinguish each other in not just their size and immune phenotype, but yet they can have a difference in a density (utilized as sucrose density gradient in ultracentrifugation), proteomic and lipidomic profiles [40] .…”
Section: Platelet-derived Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation